Enkapsulasi Ekstrak Klorofil Daun Sirsak (Annona muricata l.) pada Berbagai Konsentrasi Pelarut dengan Menggunakan Karagenan Malang - handini, handini; Nurani, Maria Puri; Gomes, Eduard (Fakultas Pertanian, 2025)
Chlorophyll is a green pigment that found generally in chloroplast mesofil leaf cell. Chlorophyll is a pigment that easily degredating. Chlorophyll degradation is caused by temperature, light intensity, or environment condition. To keep chlorophyll from degradation, the encapsulation methods can be applied. Encapsulation is a method to coating substrate or raw material such as pigment before applied in food system. The combination of coating is called encapsulation. Pigments need to encapsulated because to protect material from degradation when processing or storaging. This research purpose is to know the influence of different solvent concentration to chlorophyll amount in storaging prosess. The research use Complitely Randomized Design. Encapsulation methods using freeze dryer and measuring chlorophyll amount using spectrophotometre. Measurement of chlorophyll amount after extracting process and encapsulation process. Measurement of chlorophyll stability do within 4 weeks storaging and each week need to measure the chlorophyll amount and half life time calculation is to know the chlorophyll life time. In the encapsulation process there is reduction about 92,18% from 75,4907 ppm to 5,9018 ppm at 50 ml solvent concentration, 75 ml solvent concentration reduction is 92,63% from 66,0438 ppm to 4,8628 ppm and 100 ml solvent concentration reduction is 91,35% from 45,7894 ppm to 3,9567 ppm. Half life time calculation is shown that chlorohyll damaging is happen at 26 days for 50 ml solvent concentration, for 75 ml solvent concentration is happen at 39 days and for 100 ml solvent concentration is happen at 75 days after storaging process.